2002
DOI: 10.1590/s0037-86822002000600008
|View full text |Cite
|
Sign up to set email alerts
|

Cativeiro de aves como fonte de Cryptococcus neoformans na cidade de Campo Grande, Mato Grosso do Sul, Brasil

Abstract: Resumo Cryptococcus neoformans é a levedura capsulada causadora de criptococose em humanos e animais. A variedade neoformans, encontrada em diversas fontes ambientais, inclusive habitats de aves, é importante causa de mortalidade em indivíduos com AIDS em todo o Mundo. Contudo, ainda não há estudos sobre a sua ecologia na região Centro Oeste brasileira, onde há registro da ocorrência de casos humanos da micose. Para estudar fontes saprofíticas de C. neoformans, na cidade de Campo Grande, foram coletadas 20 amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
22

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 18 publications
1
25
1
22
Order By: Relevance
“…Occurrence of subclinical, asymptomatic forms of the disease is unknown and studies, such as cellular immunity surveys using intradermic tests with the yeast antigen in patients without clinical disease are rare, and therefore the extent of the subclinical form has not been properly evaluated 41,48 . C. neoformans' habitat in the environment is on the ground, in decomposed vegetables, bird and bat feces which are found both in urban and rural areas of Brazil 3,5,7,27,47,50,55,58,59,66,67,75,89,90 . Studies of LAZERA et al 43,44,45,46 gave new dimensions to the ecology of the cryptococcosis agent in Brazil demonstrating that yeast is associated not only to Eucalyptus sp gender, but also to other species of trees.…”
Section: Ecological and Epidemiological Aspectsmentioning
confidence: 99%
“…Occurrence of subclinical, asymptomatic forms of the disease is unknown and studies, such as cellular immunity surveys using intradermic tests with the yeast antigen in patients without clinical disease are rare, and therefore the extent of the subclinical form has not been properly evaluated 41,48 . C. neoformans' habitat in the environment is on the ground, in decomposed vegetables, bird and bat feces which are found both in urban and rural areas of Brazil 3,5,7,27,47,50,55,58,59,66,67,75,89,90 . Studies of LAZERA et al 43,44,45,46 gave new dimensions to the ecology of the cryptococcosis agent in Brazil demonstrating that yeast is associated not only to Eucalyptus sp gender, but also to other species of trees.…”
Section: Ecological and Epidemiological Aspectsmentioning
confidence: 99%
“…Besides the domestic environments, commercial stores that sell birds are prone to harbour C. neoformans due the high frequency of the conditions described above. For instance, in the city of Campo Grande, Mato Grosso do Sul, a study of bird droppings identified C. neoformans serotype A in cages of budgerigars in a commercial store (Filiú et al 2002). The original and natural budgerigar habitats are not necessarily positive for C. neoformans.…”
Section: Replymentioning
confidence: 99%
“…As amostras de excretas de C. livia foram coletadas semanalmente de locais como os parapeitos de janelas, as superfícies de ar condicionado e dos pátios internos na área acadêmica e hospitalar do Campus Saúde. As coletas foram realizadas das excretas secas, conforme descritos por diversos autores (Filiú et al, 2002;Reolon et al, 2004;Baroni et al, 2006;Contin et al, 2011), acondicionadas em frascos estéreis, transportadas ao Laboratório de Micologia da Faculdade de Medicina (FAMED-FURG) e processadas imediatamente.…”
Section: Introductionunclassified